Kualitas Pelayanan, Kualitas Produk dan Persepsi Harga Terhadap Kepuasan Pelanggan Di Hotel Aryaduta Menteng Jakarta - Anggha Pratama Purnama Putra; Ricky Talumantak (LPPM Universitas Asa Indonesia, 2022)
This study aims to analyze and determine the effect of service quality, product quality and price perception on customer satisfaction at the aryaduta menteng hotel. The background is research is the increasingly stringent business development at the aryaduta menteng hotel Jakarta. Based on the sampling technique in this study is quantitative, this sample collection technique is purposive sampling, the technique carried out by this study uses multiple linear analysis. The results of this study are service quality, product quality, price perception affect customer satisfaction simultaneously, partially service quality, product quality and price perception have a significant effect on customer satisfaction